The autotransporter protein BatA is a protective antigen against lethal aerosol infection with Burkholderia mallei and Burkholderia pseudomallei. (11th April 2019) - Lafontaine, Eric R.; Chen, Zhenhai; Huertas-Diaz, Maria Cristina; Dyke, Jeremy S.; Jelesijevic, Tomislav P.; Michel, Frank; Hogan, Robert J.; He, Biao
Abstract: Background: Burkholderia mallei and Burkholderia pseudomallei are the causative agents of glanders and melioidosis, respectively. There is no vaccine to protect against these highly-pathogenic and intrinsically antibiotic-resistant bacteria, and there is concern regarding their use as biological warfare agents. For these reasons, B. mallei and B. pseudomallei are classified as Tier 1 organisms by the U.S. Federal Select Agent Program and the availability of effective countermeasures represents a critical unmet need. Methods: Vaccines (subunit and vectored) containing the surface-exposed passenger domain of the conserved Burkholderia autotransporter protein BatA were administered to BALB/c mice and the vaccinated animals were challenged with lethal doses of wild-type B. mallei and B. pseudomallei strains via the aerosol route. Mice were monitored for signs of illness for a period of up to 40 days post-challenge and tissues from surviving animals were analyzed for bacterial burden at study end-points. Results: A single dose of recombinant Parainfluenza Virus 5 (PIV5) expressing BatA provided 74% and 60% survival in mice infected with B. mallei and B. pseudomallei, respectively. Vaccination with PIV5-BatA also resulted in complete bacterial clearance from the lungs and spleen of 78% and 44% of animals surviving lethal challenge with B. pseudomallei, respectively. In contrast, all control animals vaccinated with a PIV5 construct expressing an irrelevant antigen and infected with B. pseudomallei were colonized in those tissues. Conclusion: Our study indicates that the autotransporter BatA is a valuable target for developing countermeasures against B. mallei and B. pseudomallei and demonstrates the utility of the PIV5 viral vaccine delivery platform to elicit cross-protective immunity against the organisms.